High levels of serum macrophage migration inhibitory factor and interleukin 10 are associated with a rapidly fatal outcome in patients with severe sepsis - Chuang, Tzu-Yi; Chang, Hou-Tai; Chung, Kuei-Pin; Cheng, Hui-Shan; Liu, Chung-Yang; Liu, Yen-Chun; Huang, Hsiu-Han; Chou, Ting-Chen; Chang, Bei-Ling; Lee, Meng-Rui; Lin, Chou-Jui; Lee, Shih-Wei; et al. (International journal of infectious diseases, 2014)
The aim of this study was to delineate the association between high macrophage migration inhibitory factor (MIF) and interleukin 10 (IL-10) levels in the early phase of sepsis and rapidly fatal outcome. One hundred and fifty-three adult subjects with the main diagnosis of severe sepsis (including septic shock) admitted directly from the emergency department of two tertiary medical centers and one regional teaching hospital between January 2009 and December 2011, were included prospectively. MIF and IL-10 levels were measured and outcomes were analyzed by Cox regression analysis according to the following outcomes: rapidly fatal outcome (RFO, death within 48h), late fatal outcome (LFO, death between 48h and 28 days), and survival at 28 days. Among the three outcome groups, IL-10 levels were significantly higher in the RFO group (p < 0.001) and no significant differences were seen between the LFO and survivor groups. After Cox regression analysis, each incremental elevation of 1000 pg/ml in both IL-10 and MIF was independently associated with RFO in patients with severe sepsis. Each incremental elevation of 1000 pg/ml in IL-10 increased the RFO risk by a factor of 1.312 (95% confidence interval 1.094–1.575; p=0.003); this was the most significant factor leading to RFO in patients with severe sepsis. Patients with RFO exhibited simultaneously high MIF and IL-10 levels in the early phase of severe sepsis. Incremental increases in both IL-10 and MIF levels were associated with RFO in this patient group, and of the two, IL-10 was the most significant factor linked to RFO.